Mute Swans on the Warwickshire Avon - a study of a decline - Hardman, J A; Cooper, D R (Wildfowl, 1980)
Continuous monitoring between 1962 and 1978 of the Mute Swan Cygnus olor population of the Warwickshire Avon has revealed a severe decline, involving the reduction of non-breeders by more than half and the complete loss of the Stratford herd. Breeding pairs dropped by a third and their breeding success by a quarter. Possible factors causing the decline are discussed. For the last three years of the study, lead poisoning from ingested fishing weights was the cause of death of three-quarters of the birds. Prior to 1975 a similar proportion of swans died from an unknown cause, which in retrospect must have been due to lead. The reduced breeding success is thought to reflect a deterioration in habitat, following dredging for navigation and drainage. This and the increased boat traffic, have reduced the areas of macrophytic vegetation, causing a lack of food and an enhancement of the effect of the presence of lead fishing weights.